Face Threatening Acts (FTA) in X Comments on the Palestine Recognition by France and the UK - Lisa; Lisetyo Ariyanti; Ayunita Leliana; Adam Damanhuri (Linguistic, English Education and Art (LEEA) Journal, 2026)
This research was driven by the emergence of a variety of intense reactions on social media X (Twitter) in response to the UK and French governments' policies for recognizing the sovereignty of the Palestinian state. The aim of this study is to find out what kinds of Face-Threatening Acts (FTA) strategies are employed by online users and examine how these strategies represent the sociopolitical context. The researcher analyzed 100 units of FTA data from 73 selected comments using a descriptive qualitative method and the politeness theory framework by Brown and Levinson (1987). According to the study's findings, netizens frequently employ language in a straightforward and aggressive way, preferring the Order strategy to call for humanitarian action and the Insult strategy to undermine the legitimacy of governmental power. The findings of this study demonstrate a clear polarization in the digital realm, where the use of harsh language is encouraged by the efficiency of communication on platform X and an intense sense of moral and security urgency. The researcher came to the conclusion that when it comes with truly sensitive global issues, the boundaries of politeness are frequently ignored in order to directly communicate political demands and public anger to those in authority. Keywords: Face Threatening Acts (FTAs), Palestine Recognition, Politeness Theory, X (Twitter), Political Discourse